Technical efficiency of irrigated and rain-fed smallholder agriculture in Tigray, Ethiopia: a comparative stochastic frontier production function analysis - Gebregziabher, Gebrehaweria; Namara, Regassa E.; Holden, S. (2012)
Stochastic production frontiers of irrigated and rain-fed smallholder agriculture in Tigray, Ethiopia, were fitted to a random sample of irrigated and rain-fed plots to compare their technical efficiencies. Propensity Score Matching Method was applied to select rain-fed plots with comparable bio-physical attributes to irrigated plots that might have blurred the true efficiency differences between the two systems. Irrigated farms are on a higher production frontier with significant inefficiencies, while rain-fed farms are on a lower production frontier with high efficiency levels. Thus, there is considerable potential for increasing outputs by improving the efficiency of irrigation farms. Rain-fed systems need interventions in soil moisture management to move to a higher production frontier. The study underlines the need for correcting the sequence and mix of yield boosting technologies such as irrigation, improved seeds, and fertilizer that are promoted in arid environments such as Tigray. We recommend that water control must precede or implemented in tandem with improved seeds and fertilizer technologies. Unless soil moisture is improved by investing in moisture improving technologies, the use of seed and fertilizer in moisture stressed areas such as Tigray may have adverse effects.